GREEN HUMAN RESOURCE MANAGEMENT, SUSTAINABILITY, AND COMPETITIVE PERFORMANCE IN LQ45 FIRMS - Karsam, Karsam (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study examines the role of Green Human Resource Management, Corporate Sustainability, and Management Control Systems on the competitive performance of companies listed in the LQ45 index in Indonesia. Using an explanatory quantitative approach, secondary data was collected from the annual and sustainability reports of 20 LQ45 companies over the period 2013–2023, resulting in 200 samples. The analysis was conducted using PLS-SEM to test the direct and moderating effects. The findings indicate that Corporate Sustainability has a strong and positive impact on competitive performance, supporting the view that sustainability-oriented strategies enhance market and financial outcomes. GHRM shows a significant but negative direct effect, indicating that green HR practices in LQ45 companies have not been strategically integrated and may increase short-term costs or inefficiencies. Management Control Systems have a direct positive effect on competitive performance. MCS plays a critical moderating role: it strengthens the relationship between GHRM and competitive performance, but weakens the effect of Corporate Sustainability when control mechanisms become too rigid. This result underscores the importance of aligning sustainability initiatives and green HR with appropriate management control systems to achieve superior competitive performance.